Cadmium(II) adsorption on Cladophora crispata in batch stirred reactors in series - Özer, A; Özer, D; Dursun, G; Bulak, S (Pergamon-Elsevier Science Ltd, 1999)
In this study, the adsorption of cadmium(II) ions onto Cladophora crispata was investigated in a two-staged batch reactor. The sorption phenomenon was expressed by the Freundlich and Langmuir adsorption isotherms and these expressions were used for the calculation of the equilibrium value of the residual cadmium(II) concentration at each stage. The experimental equilibrium values were compared with the values obtained from Freundlich and Langmuir isotherm equations. These results showed that the increase in biomass quantity or the increase of X-o/V-o ratios affected the quantities of cadmium removed from aqueous solution. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: adsorption; isotherm; waste water; multi-staged reactor